Irreversible Electroporation of the Pancreas Using Parallel Plate Electrodes in a Porcine Model: A Feasibility Study. - Steffi J E Rombouts; Maarten W Nijkamp; Willemijn P M van Dijck; Lodewijk A A Brosens; Maurits Konings; R van Hillegersberg; Inne H M Borel Rinkes; Jeroen Hagendoorn; Fred H Wittkampf; I Quintus Molenaar (PLoS ONE, 2017)
Irreversible electroporation (IRE) with needle electrodes is being explored as treatment option in locally advanced pancreatic cancer. Several studies have shown promising results with IRE needles, positioned around the tumor to achieve tumor ablation. Disadvantages are the technical difficulties for needle placement, the time needed to achieve tumor ablation, the risk of needle track seeding and most important the possible occurrence of postoperative pancreatic fistula via the needle tracks. The aim of this experimental study was to evaluate the feasibility of a new IRE-technique using two parallel plate electrodes, in a porcine model.Twelve healthy pigs underwent laparotomy. The pancreas was mobilized to enable positioning of the paddles. A standard monophasic external cardiac defibrillator was used to perform an ablation in 3 separate parts of the pancreas; either a single application of 50 or 100J or a serial application of 4x50J. After 6 hours, pancreatectomy was performed for histology and pigs were terminated.Histology showed necrosis of pancreatic parenchyma with neutrophil influx in 5/12, 11/12 and 12/12 of the ablated areas at 50, 100, and 4x50J respectively. The electric current density threshold to achieve necrosis was 4.3, 5.1 and 3.4 A/cm2 respectively. The ablation threshold was significantly lower for the serial compared to the single applications (p = 0.003). The content of the ablated areas differed between the applications: areas treated with a single application of 50 J often contained vital areas without obvious necrosis, whereas half of the sections treated with 100 J showed small islands of normal looking cells surrounded by necrosis, while all sections receiving 4x 50 J showed a homogeneous necrotic lesion.Pancreatic tissue can be successfully ablated using two parallel paddles around the tissue. A serial application of 4x50J was most effective in creating a homogeneous necrotic lesion.